PEMBANGUNAN KAWASAN POS LINTAS BATAS NEGARA (PLBN) DAN DAMPAKNYA TERHADAP KEBIJAKAN KEAMANAN NASIONAL - maisondra maisondra (Institut Pemerintahan Dalam Negeri, 2023)
In 2024, the government has targeted that Indonesia will have 26 National Border Posts (PLBN). PLBN development is not only aimed at cross-border posts or offices, but will be built as a center for new regional economic growth. The presence of PLBN will improve the welfare of residents in border areas and increase the national security of the Indonesian nation. Through qualitative methods, researchers analyzed the conditions before the PLBN was built, the implementation of the PLBN area construction and the impact of the PLBN area development on national security policy. The research results show: Conditions of isolation and poverty before the PLBN Area were built, development of the PLBN area had been carried out on a large scale and there was a need for security policies in border areas so that the development of the PLBN Area was effective in increasing national security.